Tailoring Contacts for High-Performance 1D Ta2Pt3S8 Field-Effect Transistors - Jeong, Byung Joo; Choi, Kyung Hwan; Lee, Bom; Cho, Sooheon; Kang, Jinsu; Zhang, Xiaojie; Kim, Youngho; Jeon, Jiho; Bang, Hyeon Seok; Oh, Hyung Suk; Lee, Jae Hyun; Yu, Hak Ki; et al. (ACS Applied Materials and Interfaces, 2024)
Materials with van der Waals (vdW) unit structures rely on weak interunit vdW forces, facilitating physical separation and advancing nanomaterial research with remarkable electrical properties. Recently, there has been growing interest in one-dimensional (1D) vdW materials, celebrated for their advantageous properties, characterized by reduced dimensionality and the absence of dangling bonds. In this context, we synthesize Ta2Pt3S8, a 1D vdW material, and assess its suitability for field-effect transistor (FET) applications. Spectroscopic analysis and electrical characterization confirmed that the band gap and work function of Ta2Pt3S8 are 1.18 and 4.77 eV, respectively. Leveraging various electrode materials, we fabricated n-type FETs based on Ta2Pt3S8 and identified Cr as the optimal electrode, exhibiting a high mobility of 57 cm2 V-1 s-1. In addition, we analyzed the electron transport mechanism in n-type FETs by investigating Schottky barrier height, Schottky barrier tunneling width, and contact resistance. Furthermore, we successfully fabricated p-type operating Ta2Pt3S8 FETs using a molybdenum trioxide (MoO3) layer as a high work function contact electrode. Finally, we achieved Ta2Pt3S8 nanowire rectifying diodes by creating a p-n junction with asymmetric contact electrodes of Cr and MoO3, demonstrating an ideality factor of 1.06. These findings highlight the electronic properties of Ta2Pt3S8, positioning it as a promising 1D vdW material for future nanoelectronics and functional vdW-based device applications.
Keywords: 1d van der waal material; Contact electrodes; Contact engineering; Field-effect transistor; P-n junction; Performance; Physical separation; Unit structure; Van der Waal; Van der waals' forces; 1D van der Waals material; contact engineering; field-effect transistor; p−n junction; synthesis; Ta2Pt3S8